Aplikasi Penggunaan Konsentrat Pemacu Pertumbuhan untuk Penggemukan Sapi Potong di Karanganyar - Joko Riyanto; Lutojo Lutojo; Sunarto Sunarto (PRIMA: Journal of Community Empowering and Services, 2020)
Title: Application of Use of Growth Promoting Concentrates for Beef Cattle Fattening in KaranganyarMaju Utomo and Ngudi Berkah livestock farmer groups Wonorejo Village Gondangrejo Karanganyar District trying to the Simpo and Limpo cattle feedlot. The problem faced by breeders is the daily weight gain of cows 0.2 kg/head/day. For this reason, efforts are needed to increase production through the application of innovative growth-promoting concentrates made from a local feed. The purpose of the application is the use of growth-promoting concentrates. The dedicated team with the breeders jointly designs a solution to the problem by establishing a problem-solving effort through the use of growth-promoting concentrates. The methods of application include (1) instructional and dialogue through extension program activities using FGD (Focus Group Discussion) techniques, (2) evaluation of the level of knowledge and understanding of material progress, (3) training and manufacturing of growth-promoting concentrates, (4) ongoing monitoring and evaluation. Conclusion the application of the use of growth-promoting concentrates in cattle fattening efforts has an impact on accelerating the time of fattening from 4 months to 2 months (50%), increasing weight gain from 0.25 kg / head / day to 0.83 kg / head / day ( 67.8%), an increase in livestock farmers' income from Rp 1,416,000 to Rp 2,376,000 (235.6%), profits from farmers increased from Rp 891,050 to Rp 1,390,450 (56%). The use of growth promoters concentrate innovation to increase production and maximize the potential of genetically superior cattle breeder crosses also increase revenue.